Determination of the influence of the tape tension and the detachment force of the Velcro fastener in the rehabiliation footwear - Shchutska, Ganna; Ponomarenko, Tatyana (Technology audit and production reserves, 2018)
The object of research is the constructive parameters of orthopedic postoperative footwear, which are based on complex theoretical and experimental studies of the effect of the upper outer surface of the foot on the top of the footwear during using. One of the most problematic places is the lack of knowledge of the conditions of interaction of the supporting belts with the Velcro fastener and the outer part of the freebie. It is needed to ensure the operational reliability of shoes. In the course of the study, graphical dependencies of the change in the force of pressure on the upper part of postoperative orthopedic shoes were used when bending the sole as a function of the inclination angle between the tangent to the foot of the footwear and the support area. The forces of load R on the upper end of the postoperative orthopedic footwear are determined when the forces of friction between the lateral surfaces of the freebie and the external lateral sides of the foot are neglected. In this case, the problem is reduced to the construction of the equilibrium equations of the plane system of forces. As the practice of using the Velcro fastener shows, with the increase of the tension of the supporting belt (with the loops), the force of detachment in the beginning increases to some maximum, and then, with increasing tension, the force of detachment decreases practically to zero. This circumstance may affect the reliability of the connection of the tops of orthopedic footwear. To ensure the strength of the fastener, it is necessary to choose the type of fastener, the width and the length of the active coupling area, the density of the hooks, which will ensure the reliability of the fastener in the shoes. The optimal design features and the greatest value of the pressure force on the upper part of postoperative footwear at bending of the sole observed at an angle γ=25º are obtained. This is due to the fact that the proposed material has a number of features, in particular the good density of hooks per cm2.